2022
DOI: 10.1111/jog.15292
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of the shock index for severe postpartum hemorrhage in high‐income countries: A systematic review and meta‐analysis

Abstract: Aim: The shock index has been suggested as a screening tool for predicting postpartum hemorrhage (PPH); however, there is little comprehensive evidence regarding its predictive accuracy. This systematic review and meta-analysis aim to investigate the predictive accuracy of the shock index for severe PPH in highincome countries. Methods: A comprehensive search was conducted on MEDLINE, Cochrane Central Register of Controlled Trials, and Web of Science (from inception to June 2021). Studies assessing the predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…a population substantially different from the one we studied. [18][19][20][21][22] Only a few studies have investigated the predictive performance of SI as an early predictor of PPH in a general population of women vaginal delivery including non-PPH women. 16,27,39 Most of these studies reported AUROC values for postpartum SI to discriminate blood loss ≥1000 ml higher than our findings, 16,27 with AUROC values of 0.70 or higher, a range considered acceptable by most authors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…a population substantially different from the one we studied. [18][19][20][21][22] Only a few studies have investigated the predictive performance of SI as an early predictor of PPH in a general population of women vaginal delivery including non-PPH women. 16,27,39 Most of these studies reported AUROC values for postpartum SI to discriminate blood loss ≥1000 ml higher than our findings, 16,27 with AUROC values of 0.70 or higher, a range considered acceptable by most authors.…”
Section: Discussionmentioning
confidence: 99%
“…SI has mainly been explored as a predictor of adverse outcomes (maternal death, near‐miss, severe morbidity, transfusion, intensive care unit admission) in women with ongoing PPH, i.e. a population substantially different from the one we studied 18–22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations